IMPROVING THE QUALITY OF LEARNING THROUGH LEARNING MEDIA DEVELOPMENT - Widodo, Yono Dwi; Anas, M.; Muchson, M. (PUSAT KEWIRAUSAHAAN UNIVERSITAS BALIKPAPAN, 2024)
Learning media is part of the communication process which has an important role in the teaching and learning process. Learning media has the aim of connecting interactions between teachers and students. Interaction through learning media can help students understand the material presented by the lecturer more effectively (Sena & Howard, 2019). The research method is based on the development of the ADDIE model. The ADDIE model has five stages starting from analysis, design, development, implementation and evaluation. The interview method is used as a procedure for finding problems. Interviews were conducted with resource teachers in the Creative Entrepreneurship Products subject and class XII students. Based on the objectives and problem formulation that have been prepared above, the research method uses qualitative methods which are descriptive statistics. This Canva-based module is very suitable for use as a learning tool for Creative Products and Entrepreneurship subjects in class XII, especially for KD in making promotional media. This is shown by the validation scores of the two experts, which reached a score of 88% which is considered very valid. Research shows that Canva-based learning media consists of materials related to creating media to promote creative and entrepreneurial products. 2) Canva-based learning media is valid for use in the teaching and learning process, as shown by validation results from material experts of 86 percent (Very Valid) and the results from media experts were 90 percent (Very Valid).